2020
DOI: 10.18805/ijar.b-4223
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Effects of Docetaxel and Gene Expression of Epidermal Growth Factor Receptor During Regression of Mammary Tumours in Canines

Abstract: Background: In this study the chemotherapeutic effects of docetaxel and gene expression of epidermal growth factor receptor (EGFR) during regression of mammary tumour in canines were evaluated.Methods: Sixteen dogs suffering from canine mammary tumour were randomly divided into two groups viz. I and II and subjected to Docetaxel @ 30mg/m2 weekly, four consecutive cycles, (Group I) and surgical excision of tumour followed by chemotherapy with Docetaxel @ 30mg/m2 weekly, four consecutive cycles, (Group II). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, there are few reports on the repair of intestinal epithelial injury in chicken by MSM. Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein belonging to erbB receptor tyrosine kinase family (TKs), which are related to cell growth, proliferation, differentiation, survival, adhesion, invasion and angiogenesis (Herbst, 2004;Upadhyay et al, 2022). Studies have shown that abnormal expression of EGFR is strongly associated with tumor cell proliferation, invasion, metastasis and apoptosis inhibition (Kersting et al, 2018;Wee and Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few reports on the repair of intestinal epithelial injury in chicken by MSM. Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein belonging to erbB receptor tyrosine kinase family (TKs), which are related to cell growth, proliferation, differentiation, survival, adhesion, invasion and angiogenesis (Herbst, 2004;Upadhyay et al, 2022). Studies have shown that abnormal expression of EGFR is strongly associated with tumor cell proliferation, invasion, metastasis and apoptosis inhibition (Kersting et al, 2018;Wee and Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%